(untitled) (Hematology Meeting Reports, 2009)
von Willebrand disease (VWD) is the most common inherited bleeding disease in humans, resulting in a clinical condition in which excessive mucocutaneous bleeding is the major manifestation. Significant progress has been made in the past decade in defining the molecular genetic basis of this condition. The gene that encodes von Willebrand factor (VWF) is located on chromosome 12p and comprises 52 exons spanning 178 kb of genomic sequence. Of the two quantitative forms of the disease, types 1 and 3 VWD, significantly more is known of the molecular causation of severe type 3 disease in which a null VWF phenotype exists. Reports of gene deletions, insertions, nonsense mutations splicing defects and some missense mutations have all been documented in type 3 patients. In contrast, knowledge of the molecular pathology of type 1 disease is less advanced, although two recent, large population studies have indicated that a heterogeneous collection of missense mutations is associated with the disease in 75% of cases. However, in some type 1 cases no mutations have been found in the VWF gene indicating that other genetic loci also contribute to this condition. In types 2A, 2B and 2M VWD, dominantly acting missense mutations predominate. In type 2A disease, two principal pathogenetic mechanisms have been defined: a failure to synthesize high molecular weight VWF multimers due to mutations in the VWF propeptide, D3 and A2 domains and the C-terminal knot region or an increased susceptibility to ADAMTS13-mediated proteolysis due to mutations adjacent to the cleavage site in the A2 domain. Types 2B and 2M disease are VWD variants in which gain-of-function and loss-of-function platelet-dependent phenotypes are documented, respectively. Both subtypes are due to heterozygous missense mutations affecting the glycoprotein Ib binding A1 domain of VWF. Finally, type 2N disease is a recessive disorder in which missense mutations affect the factor VIII binding domain at the N-terminus of the VWF monomer (D’ and D3 domains).